TRADISI ARISAN PERNIKAHAN SEBAGAI SISTEM PERTUKARAN SOSIAL DI DALAM PELAKSANAAN PESTA PERNIKAHAN (Studi pada Masyarakat di Desa Tanjung Balau Kecamatan Serasan Kabupaten Natuna) - Enji Epriadi; Sri Wahyuni; Nanik Rahmawati (LPPM STISIP Persada Bunda, 2024)
The implementation of a traditional wedding ceremony is an event that requires considerable funding, overcoming the problem of financing the wedding, therefore the people in Tanjung Balau Village, Serasan District, Natuna Regency have given birth to various traditions, one of which is the wedding arisan, or often referred to as (Pesatuan). Geographical location, the amount given will remain the same and people in other villages may also participate so that this is interesting to study and is a difference from previous research. The purpose of this study was to find out how the wedding arisan tradition was carried out as a system of social exchange in the implementation of weddings (Studies in Communities in Tanjung Balau Village, Serasan District, Natuna Regency). The method used in this study is a qualitative descriptive method with as many as 10 informants and uses data collection techniques and tools in the form of observation, interviews, and documentation. The data analysis technique uses Social Exchange Theory by Thibaut and Kelley. The results of the study found that in this study, namely this social gathering, it had been running for Â± 60 years to date. The wedding arisan in Tanjung Balau Village has several types of arisan including rice, sugar, fish, eggs, oil, wood, mineral water, single organ and seserahan arisan from proposing to marriage and each type of arisan has its own chairman. Each type of arisan has Â±100 members or participants, and each participant may join more than one type of arisan as long as it is according to ability. If you donate rice you have to return rice, you donate oil you have to return oil, you donate sugar you have to return sugar with the same measure and amount. This wedding arisan tradition in the implementation of the wedding ceremony is a form of social exchange that occurs between members of the arisan. The pressures faced by members of the wedding arisan are by means of social control (preventive) which are not written but these are considered rules and norms that must be followed to prevent unwanted things from happening in the.